US and CT of the Liver after Electric Shock - Amela Sofić; Nermina Bešlić; Alma Efendić; Aladin Čarovac; Jusuf Šabanović; Elma Jahić; Melika Bukvić; Fikreta Krakonja; Jana Kupusović (Case Reports in Radiology)
Liver injuries caused by high voltage electricity are rare and result in high mortality and morbidity. They are produced by the resistance to the passage of electrical current through the tissue, which creates heat that leads to coagulation necrosis and rupture of the cell membrane. We present a case of an electrical injury to the liver, diagnosed by ultrasound and CT in a 39-year-old man who presented with skin burns on his right hand and right hemiabdomen. Injuries occurred after the contact with 220 kV high voltage electricity.